Pendampingan Kalibrasi Arah Kiblat Bagi Imeum Chik di Provinsi Aceh: Qibla Direction Calibration Assistance for Imeum Chik in Aceh Province - Machzumy, Machzumy; Mahli, Mahli (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Determining the qibla direction is a topic that also captures public attention. Issues arise among the public when rechecking the qibla direction, leading to various doubts, especially among the people of Aceh province. Based on initial investigations by the facilitator regarding the qibla direction of several mosques in Aceh province, it was found that, on average, the qibla direction of mosques deviates from the direction of the Kaaba. The research problem formulated is: